Climber, mediator, and marathoner: narrative inquiry of career motivation changes of pre-service CSL teachers throughout teaching practicum - Zhou, Rubing; Wang, Tianmiao; Lin, Hanzhao (Frontiers in Psychology, 2024)
Introduction The growing global demand for foreign language learning contrasts sharply with the shortage of second language teachers. In Chinese as a second language (CSL) education, although the number of pre-service CSL teachers is increasing, few continue in the profession after completing their teacher education courses. Methods To investigate the reasons behind this trend, this longitudinal narrative inquiry examined the career motivations of three participants during their teaching practicum. The study focused on identifying key narrative clues based on metaphors emerging from their narratives. Results The research found that the participants’ career motivations were influenced by their teaching practice and experienced various dynamic changes. Key motivational factors included self-efficacy and intrinsic self-fulfillment, with a notable influence from the unique cross-cultural motivation associated with second language teaching. Discussion The study underscores the significant role of narratives and metaphors in understanding changes in teacher career motivations. It suggests that enhancing self-efficacy and intrinsic motivation, alongside recognizing cross-cultural motivations, could be crucial in addressing the retention issues among pre-service CSL teachers.